Cu2+ recognition by N, N′-benzylated bis(amino amides). Issue 8 (7th February 2017) - Gorla, Lingaraju; Martí-Centelles, Vicente; Altava, Belén; Burguete, M. Isabel; Luis, Santiago V.
Abstract : N -Benzylation of C 2 -symmetric pseudopeptides affects to their coordination properties and provides an interesting and selective CD answer towards Cu 2+ ions. Abstract : Two new C 2 -symmetric N, N ′-benzylated bis(amino amides) have been synthesised and their interaction with different transition metals studied using a variety of techniques including UV-Vis and CD spectroscopy or ESI-MS. The determination of the corresponding stability constants with Cu 2+ has been possible, in H2 O/CH3 CN 7/3 v/v, for one of these ligands (4 ) using potentiometric titrations. The results obtained reveal that N -benzylation affords significant changes to their properties and is accompanied by an appreciable decrease in the corresponding complexation stability constants. However, this, along with the low kinetics associated to Ni 2+, facilitates the recognition of Cu 2+ by4 that can be followed by the naked-eye up to the submillimolar range. Very interestingly, the chiral nature of this ligand provides an intense and well defined CD curve for the corresponding Cu 2+ complex, very sensitive to the coordination geometry, facilitating the analysis of this interaction even at the μM range. The formation by both ligands (3 and4 ) of square planar complexes with Cu 2+ and Ni 2+ displaying a 1 : 1 stoichiometry was confirmed by their X-ray crystal structures.